Identification of Protein Bands Characteristic of Raw and Boiled Beef and Pork Meat Using the Sodium Dodecyl Sulphate Polyacrylamide Gel Electrophoresis (SDS-PAGE) Method - Roswiem, Anna P.; Pedrianto; Arifandi, Firman (International Journal of Halal Research, 2023)
The second most abundant nutrient content in animal meat is protein, which is in the range (16-22) %. Proteins are denatured by heat. Protein denaturation will changes in protein structure. The Sodium Dodecyl Sulphate Polyacrylamide Gel Electrophoresis (SDS-PAGE) method aims to determine the composition of proteins based on their molecular weight (MW). Therefore, the aim of this research is to determine the differences in protein band profiles that characterize pork and beef meat, raw or boiled, based on their MW. The research began with the isolation of protein from pork and beef meat, both raw and boiled. Next, the protein isolate produced from each sample was precipitated by adding ammonium sulfate with saturation of 20, 40, 60, and 80%. Then the protein formed was purified by dialysis method and the protein bands were characterized with 10% (v/v) SDS-PAGE. To determine the MW of protein, MW calculations were performed using PhotoCaptMW software, which using a protein with a MW of 10 kDa to 250 kDa as a marker for the MW of the protein. The results showed that the number of protein bands from raw pork and beef meat was greater than the number of protein bands from boiled meat. There are 23 protein bands that characterize raw pork which are not present in raw beef, with a range of MW (3.462-69.068) kDa; and the characteristic protein bands of raw beef which are not present in raw pork are 18 bands, with MW range of (15,445-291,176) kDa. The characteristic protein bands for boiled pork which are not present in boiled beef are 9 bands with a MW range of (2.692-19.659) kDa. There are 4 protein bands that characterize boiled beef which are not present in boiled pork with a MW of: 15,942; 16.133; 16,041 and 16,272 kDa.